2018
DOI: 10.5194/acp-18-13215-2018
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of atmospheric aerosol in a marine dusty environment by ionic/composition mass balance (IMB)

Abstract: PM 10 aerosol was sampled in Santiago, the largest island of Cabo Verde, for 1 year, and analysed for elements, ions and carbonaceous material. Very high levels of dust were measured during the winter months, as a result of the direct transport of dust plumes from the African continent. Ionic and mass balances (IMBs) were applied to the analysed compounds, permitting the determination of six to seven different processes and source contributions to the aerosol loading: insoluble and soluble dust, sea salt, carb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…The higher values observed in this study are mainly due to the influence of Saharan dust during the sampling period. The particulate matter mass concentration during the sampling period was up to 145 µg/m³, indicating a strong influence of Saharan dust.However, the values of this study are within reported range for mineral dust dominated particulate matter(Cardoso et al, 2018;Patey et al, 2015) .…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The higher values observed in this study are mainly due to the influence of Saharan dust during the sampling period. The particulate matter mass concentration during the sampling period was up to 145 µg/m³, indicating a strong influence of Saharan dust.However, the values of this study are within reported range for mineral dust dominated particulate matter(Cardoso et al, 2018;Patey et al, 2015) .…”
supporting
confidence: 82%
“…The observed concentrations were found to be within the range of concentrations previously observed in this region, especially for PM10 elemental concentrations. Cardoso et al (2018) (Prost et al, 2017).…”
Section: Size Resolved Aerosol Measurementsmentioning
confidence: 99%
“…Therefore, inferences based on bibliographic information have to be assumed, to totally apportion the measured particulate mass. A thorough discussion about the IMB principles and constraints is presented in Cardoso et al, (2018). In that publication the methodologies for the sequential apportionment of the total aerosol mass were also fully detailed.…”
Section: Ionic and Mass Balance Methodologiesmentioning
confidence: 99%
“…These methods successfully allowed to apportion fractions of the measured aerosol to sources and formation processes, including secondary inorganic and organic formation, or biomass burning during wild fires and residential heating. In a recent publication, these different scrutinizing methodologies were used to evaluate, for the first time, the sources and formation processes contributing to the total aerosol Particulate Mass (PM) (Cardoso et al, 2018). This technique was called Ion and Mass Balance (IMB) and was applied to the PM10 aerosol apportionment in a background marine environment frequently affected by strong Saharan dust intrusions, but with low levels of carbonaceous matter (Cape Verde Islands).…”
Section: Introductionmentioning
confidence: 99%
“…The selected metals (i.e., Al, Ti, Ba, Se, Li, As, Fe, Zn, Cu, Mn, and Si) in coarse PM can be emitted by a wide range of sources including soil, road dust, brake and tire wear, and industrial emissions [22,27,73,74]. As shown in the figure, the concentrations of Al, Si, and Fe, as tracers of soil dust [27,75], were significantly higher in the warm season compared to the colder season at the Tohid retirement home (p value < 0.05). This is due mainly to the higher wind speeds and lower relative humidity's in the warm seasons that facilitate the resuspension of soil particles [59,76].…”
Section: Data Overviewmentioning
confidence: 99%